Electrochemical migration of silver in electronics applications - Mena, Manolo G. (Philippine Engineering Journal)
Silver (Ag) filler is the most attractive choice among all the conductive fillers. However, silver electrochemically migrates in the presence of moisture and applied bias. In microelectronic devices, silver migration usually occurs between adjacent conductors/electrodes, which leads to the formation of dendrites and eventually results in short-circuit failure. An investigation for two types of fillers was done using the water drop test and a 1000-hour temperature-humidity-bias (THB) test. Four different bias voltages and six different distance spacings were used for each of the two fillers. The higher voltage requirement for Ag migration to occur for epoxy A than for epoxy C was attributed to the high volume resistivity of epoxy A. It was discovered that an electric field value of more than 1 volt/mm will start Ag migration.